The Expression Regulatory Network in the Lung Tissue of Tibetan Pigs Provides Insight Into Hypoxia-Sensitive Pathways in High-Altitude Hypoxia - Yang, Yanan; Yuan, Haonan; Yang, Tianliang; Li, Yongqing; Gao, Caixia; Jiao, Ting; Cai, Yuan; Zhao, Shengguo (Frontiers in Genetics, 2021)
To adapt to a low-oxygen environment, Tibetan pigs have developed a series of unique characteristics and can transport oxygen more effectively; however, the regulation of the associated processes in high-altitude animals remains elusive. We performed mRNA-seq and miRNA-seq, and we constructed coexpression regulatory networks of the lung tissues of Tibetan and Landrace pigs. HBB, AGT, COL1A2, and EPHX1 were identified as major regulators of hypoxia-induced genes that regulate blood pressure and circulation, and they were enriched in pathways related to signal transduction and angiogenesis, such as HIF-1, PI3K-Akt, mTOR, and AMPK. HBB may promote the combination of hemoglobin and oxygen as well as angiogenesis for high-altitude adaptation in Tibetan pigs. The expression of MMP2 showed a similar tendency of alveolar septum thickness among the four groups. These results indicated that MMP2 activity may lead to widening of the alveolar wall and septum, alveolar structure damage, and collapse of alveolar space with remarkable fibrosis. These findings provide a perspective on hypoxia-adaptive genes in the lungs in addition to insights into potential candidate genes in Tibetan pigs for further research in the field of high-altitude adaptation.